Community perception and stewardship of public coastal infrastructure in Cedar Key, Florida - Li, Jiayang; Abukhalaf, Amer Hamad Issa; Bean, Eban; Brisotto, Carla; Clark, Mark W.; Von Meding, Jason; Otalora, Andrea; Barry, Savanna (Frontiers in Marine Science, 2025)
This study contributes to empirical evidence about how local communities may perceive and steward nature-based coastal infrastructure developed in the public realm to enhance coastal resilience. Coastal communities increasingly face flood risks driven by chronic erosion, habitat degradation, and climate change. Nature-based coastal infrastructure-such as living shorelines-offers promise for hazard mitigation, resilience, and co-benefits. However, public awareness and acceptance remain barriers to broader adoption, and little is known about perception of community-level coastal infrastructure beyond private settings. This study used an intercept survey (N = 155) in Cedar Key, Florida, U.S., to investigate public perceptions of various coastal infrastructure options across the green-gray spectrum, community stewardship of coastal infrastructure in terms of funding and maintenance, and potential factors that predict more positive perceptions of nature-based options and stronger lay stewardship. Among the five types of coastal infrastructure that we examined (i.e., vegetation-only, sills, beach nourishment, revetment, and sea wall), participants rated nature-based options (vegetation-only and sills) significantly higher for beauty. However, contrary to existing literature, we found no significant differences in perceived protection between nature-based and hardened options. Instead, beauty and protection ratings were strongly correlated for all options except sea walls. More favorable views of nature-based options were associated recognizing shoreline’s role in pollutant capture and having more pro-environmental attitudes. Findings also suggest that sills were seen as more effective than vegetation-only for erosion control and protection. Additionally, over 45% of self identified residents reported feeling responsible for maintaining coastal infrastructure significantly more than non-residents-while over 40% of tourists indicated responsibility for funding-significantly more than non-visitors. Shore-based anglers also emerged as promising stewards, expressing support for both funding and maintenance. These findings contribute to understanding public perception and potential stewardship of nature-based coastal infrastructure at the local level and inform designs that can gain stronger community preference and support.